Explicit metalinguistic knowledge at work : the case of spontaneous written production by formal adult Chinese learners of English - Hu, Guangwei. (2008)
An issue of great controversy in second language acquisition (SLA) research has been the status of second language (L2) learners' explicit metalinguistic knowledge (i.e. more or less consciously represented and verbalisable knowledge of L2 grammar) in their acquisition and use of the target language. Most teachers and learners in formal contexts of L2 instruction believe that such knowledge is indispensable. SLA theorising, on the other hand, fails to provide a consensual view in this regard. To further complicate the issue, empirical studies, limited in quantity, have yielded inconsistent findings. Yet, a clear understanding of the role of explicit metalinguistic knowledge in L2 performance bears crucially on effective language instruction. The present study aims to produce empirical evidence for a critical evaluation of the intuitive beliefs and perceptions held by L2 teachers and learners with respect to metalinguistic awareness, to test a number of hypotheses derived from current theoretical claims about the role of explicit metalinguistic knowledge in spontaneous production, and to corroborate and supplement relevant empirical findings documented in the SLA literature. It addresses the questions of whether explicit metalinguistic knowledge facilitates spontaneous L2 use; whether the usefulness of such knowledge is subject to variation across different tasks and contexts of use; and what cognitive processes promote or constrain access to, and application of, such knowledge in L2 production.